RELATIONSHIP OF RELATION WITH FRIENDS OF THE SAME AGE TO PERSONAL HYGIENE DURING MENSTRUATION ON GIRL TEENAGE IN PONDOK PESANTREN MUHAMMADIYAH MANAFI’UL ULUM SAMBI BOYOLALI - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Background : health reproduction is the physical health, mentally, and social welfare and also the reproduction process. Teenagers have to know about the health of reproduction. Female teenager in 15-19 years old, almost of them discussed about the health of reproduction with peers. The less discipline and careless of female teenagers on the cleaness of themselves while menstruation Objective : knowing the relation between peers toward personal hygiene during menstruation in female teenager at Muhammadiyah Manafi?ul Ulum Boarding School Sambi Boyolali. Method : there was a analytical observational research with quantitative cross sectional research design. The sample in this research was all of the female teenager that lived at Muhammadiyah Manafi?ul Ulum Boarding School Sambi Boyolali about 36 female teenagers. The sample technique is totally sampling with fullfill inklusion and eksklusion, criteria there was 30 sample of female teenagers. Questionnaire used to measure of relationship with the peers and personal hygiene during menstruation. The data analysis used spearman rank. Result : there was relation with peers toward personal hygiene during menstruation in female teenager at Muhammadiyah Manafi?ul Ulum Boarding School Sambi Boyolali with p value 0,034 (p < 0,05). Conclusion: the better relation with peers, means that personal hygiene better than before during menstruation in female teenager.